Can the QuickDASH PROM be Altered by First Completing the Tasks on the Instrument?. Issue 9 (September 2019) - Shapiro, Lauren M.; Harris, Alex H.S.; Eppler, Sara L.; Kamal, Robin N.
Abstract: Background: Health systems and payers use patient-reported outcome measures (PROMs) to inform quality improvement and value-based payment models. Although it is known that psychosocial factors and priming influence PROMs, we sought to determine the effect of having patients complete functional tasks before completing the PROM questionnaire, which has not been extensively evaluated. Questions/purposes: (1) Will QuickDASH scores change after patients complete the tasks on the questionnaire compared with baseline QuickDASH scores? (2) Will the change in QuickDASH score in an intervention (task completion) group be different than that of a control group? (3) Will a higher proportion of patients in the intervention group than those in the control group improve their QuickDASH scores by greater than a minimally clinically important difference (MCID) of 14 points? Methods: During a 2-month period, 140 patients presented at our clinic with a hand or upper-extremity problem. We approached patients who spoke and read English and were 18 years old or older. One hundred thirty-two (94%) patients met the inclusion criteria and agreed to participate (mean ± SD age, 52 ± 17 years; 60 men [45%], 72 women [55%]; 112 in the intervention group [85%] and 20 in the control group [15%]). First, all patients who completed the QuickDASH PROM (at baseline) were recruited for participation. Intervention patients completed the functional tasks on the QuickDASH and completed a followup QuickDASH. Control patients were recruited and enrolled after the intervention group completed the study. Participants in the control group completed the QuickDASH at baseline and a followup QuickDASH 5 minutes after (the time required to complete the functional tasks). Paired and unpaired t-tests were used to evaluate the null hypotheses that (1) QuickDASH scores for the intervention group would not change after the tasks on the instrument were completed and (2) the change in QuickDASH score in the intervention group would not be different than that of the control group (p < 0.05). To evaluate the clinical importance of the change in score after tasks were completed, we recorded the number of patients with a change greater than an MCID of 14 points on the QuickDASH. Fisher's exact test was used to evaluate the difference between groups in those reaching an MCID of 14. Results: In the intervention group, the QuickDASH score decreased after the intervention (39 ± 24 versus 25 ± 19; mean difference, -14 points [95% CI, 12 to 16]; p < 0.001). The change in QuickDASH scores was greater in the intervention group than that in the control group (-14 ± 11 versus -2 ± 9 [95% CI, -17 to -7]; p < 0.001). A larger proportion of patients in the intervention group than in the control group demonstrated an improvement in QuickDASH scores greater than the 14-point MCID ([43 of 112 [38%] versus two of 20 [10%]; odds ratio, 5.4 [95% CI, 1 to 24%]; p = 0.019). Conclusions: Reported disability can be reduced, thereby improving PROMs, if patients complete QuickDASH tasks before completing the questionnaire. Modifiable factors that influence PROM scores and the context in which scores are measured should be analyzed before PROMs are broadly implemented into reimbursement models and quality measures for orthopaedic surgery. Standardizing PROM administration can limit the influence of context, such as task completion, on outcome scores and should be used in value-based payment models. Level of Evidence: Level II, therapeutic study.